RESPON HARGA PRODUSEN TERHADAP PERUBAHAN HARGA KONSUMEN BAWANG MERAH DI INDONESIA - Illia Seldon Magfiroh; Ahmad Zainuddin; Intan Kartika Setyawati; Rena Yunita Rahman (University of Jember, 2017)
High price fluctuations in onions can cause prices at the consumer level to change in a relatively quick time. However, the price change is not necessarily enjoyed by most of the onion farmers. This implies a high marketing margin and low farmer prices. This study aims to analyze the integration of onion consumer market with onion producer market in Indonesia by using VECM (Vector Error Correction Model). Monthly onion price data with 48 time series period is used to analyze the onion market integration. The results show that only the consumer market that affects the market of onion producers (one way). There are short-term and long-term market integration between the consumer market and the onion producers. However, changes that occur in the consumer market are not always accepted by the onion producers of the same scale. This shows that the price information of onion in the producer's market is not always transmitted perfectly to the onion producer market.